2023
DOI: 10.3389/fmed.2023.1094937
|View full text |Cite
|
Sign up to set email alerts
|

Myopic tilted disc: Mechanism, clinical significance, and public health implication

Abstract: Myopic tilted disc is a common structural change of myopic eyes. With advancing ocular imaging technology, the associated structural changes of the eye, particularly the optic nerve head, have been extensively studied. These structural changes may increase patients’ susceptibility to axonal damage and the risk of developing serious optic neuropathies including glaucoma. They also lead to diagnostic difficulties of disease suspects and treatment dilemmas of patients, which implicate clinical practice and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…Various studies have investigated the impact of myopic tilted disc on structural change of optic nerve. Fan et al found that eyes with torted disc exhibited thicker temporal retinal and RNFL and more temporally positioned superior peak of RNFL [ 20 ], and during the myopic shift, the tilting and rotation of optic disc may be accompanied by nasal bulging and kinking of retinal nerve fibers [ 21 ]. Therefore, it could result in vessel density of the inside optic disc and temporal quadrant does not descend.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have investigated the impact of myopic tilted disc on structural change of optic nerve. Fan et al found that eyes with torted disc exhibited thicker temporal retinal and RNFL and more temporally positioned superior peak of RNFL [ 20 ], and during the myopic shift, the tilting and rotation of optic disc may be accompanied by nasal bulging and kinking of retinal nerve fibers [ 21 ]. Therefore, it could result in vessel density of the inside optic disc and temporal quadrant does not descend.…”
Section: Discussionmentioning
confidence: 99%
“…PHOMS corresponded to the early abnormal visual field and 46.7% of affected eyes had persistent visual field defects after refractive correction, possibly due to damaged axoplasmic transport caused by prolonged bending of nerve fibers ( 8 ). In addition to TDS, an acquired tilted disc caused by scleral stretching is also a feature of myopia ( 44 ). Lyu et al ( 45 ) reported for the first time that PHOMS were significantly associated with the degree of myopia and the magnitude of ONH tilt angle in children.…”
Section: Phoms and Associated Diseasesmentioning
confidence: 99%